PENINGKATAN KEMAMPUAN GURU MATEMATIKA SMK DALAM MENGEMBANGKAN KOMUNIKASI MATEMATIK DI KELAS MELALUI PENDAMPINGAN DENGAN PENDEKATAN LESSON STUDY SEMESTER GENAP TAHUN 2014/2015 - Syakur, Ahmad Abdul (Jurnal Penelitian Pendidikan, 2015)
One of the discoveries in the academic supervision is math teacherdifficult in developing mathematical communication in the classroom, this causes the math achievement unsatisfied. Purpose of research is to improve the ability of teachers to develop mathematical communication in the classroom through assistance with lesson study approach. The research was conducted in two cycles. The research result is improvement activity of lesson plans 7%, 10% mathematical communication skills, and student achievement 6%. Supervisor suggested using mentoring lesson study on the activities of academic supervision.Keywords: mathematical communication, lesson study, and academic supervision.